Capacidades combinatórias, heterose e depressão por endogamia de híbridos comerciais de milho - Senhorinho, Henrique José Camargo (2014)
With the objective to evaluate the general and specific combining abilities, heteroses and inbreeding depression in twenty two commercial hybrids, two groups of parents from different companies were crossed in a partial diallel scheme throught it´s 96 hybrid combinations. They were evaluated in a partial balanced square lattice design with intrablock analysis with recovery of interblock informations along with their parents, first generation of inbreeding of these parents and four controls, in two growing seasons, 2011/2012 and 2012/2013, in Sabáudia/PR. Four agronomic traits were evaluated: grain yield, plant height, earheight and frequency of poor hulled ears. The analysis of variance were applied on the experimental data. Through the adjusted means, Griffing (1956) diallel analysis methodology were applied on the experimental data, in order to measure the general and specific combining abilities. Not a single genotype combined several desirable traits, so discussion was assessed for each character. The commercial hybrids 30B39, 30K64 and 30B30 showed outstanding GCA for grain yield, while hybrids 30F53 and P1630 for plant height, AG9040 and AG7010 for ear heights and AG7010 for poorly hulled ears, in which are recommended for the synthesis of composts followed by a intrapopulation breeding programs. The hybrids 30B39 x AG8088, 30B39 x AG9045 e P1630 x AG8021 showed desirables values of SCA for grain yield, plant and ear heights and are recommended for reciprocal recurrent selection programs. It was also detected high levels of inbreeding depression for grain yield, and lower levels for plant and ear heights, indicating that, for grain yield, loci with non-additive effects were important to it. Therefore, interpopulational breeding methods are recommended.